Manajemen Sekolah Islam Terpadu (Pengembangan Kurikulum Sekolah Islam Terpadu) - Sistupani, Sistupani (BASICA, 2023)
The presence of Integrated Islamic Schools with their integrated curriculum is a new phenomenon in the form of the Islamic education system in Indonesia. Until the end of the 70s, the Indonesian education system still had a dichotomous style. As the Reformation progressed in the 80s, there were efforts by some groups to try to break away from the existing system with the idea of ​​an Integrated Islamic School. This research focuses on revealing how the presence of Integrated Islamic Schools has contributed to the development of Islamic education in Indonesia. This research is a qualitative case study with a descriptive approach. It is hoped that the results of this research will be useful for all parties who wish to know about the existence and development of Integrated Islamic Schools in the development of Islamic education in Indonesia. This research found that the emergence of Integrated Islamic Schools, with all their variations, in the development of Islamic education in Indonesia was initiated by Islamic movement activists who were anxious about the results of school graduates in Indonesia. Where the graduates do not have strong resistance to the currents and viruses of globalization, because the school education system in Indonesia is dichotomous, mastering worldly sciences but not having a strong religious spirit, vulnerable to the influence of the globalization virus, far from Islamic values. This condition is felt to be not good for the future of the Indonesian Muslim generation. So, the alternative and solution needs to be to reconstruct the existing education system using an integrated Islamic education system. The development of an integrated school curriculum certainly uses good and appropriate management, known as school management, which regulates the school planning system, organization, implementation of school activities, and of course the evaluation process which is expected to be able to build healthy and advanced school institutional dynamics. Apart from that, it is necessary to carry out quality control to maintain the institutional quality of both teachers, education staff and students who focus on controlling the input, process and output.